Forest land-use change affects soil organic carbon in tropical dry forests of the Peruvian Amazon - Geomar Vallejos Torres; Andi Lozano-Chung; Luis Ordoñez-Sánchez; Patricia García-Gonzales; Aníbal Quinteros; Nery Gaona-Jimenez; Wilfredo Mendoza-Caballero; Wilder Macedo-Córdova; Jorge Saavedra-Ramirez; Juan R. Baselly-Villanueva; César Marín (Forest Systems)
Aim of study: The loss of forest cover is a global problem that alters ecosystems, contributing to carbon emissions. This study measured the soil organic carbon (SOC) at different soil depths in tropical dry forests of the Huallaga Central in the Peruvian Amazon.